'Ugly and smelly or useful insect hunters?' Perceptions of and attitudes towards bats in the turn of the twentieth-century public sphere in Barcelona. (January 2023) - Carandell Baruzzi, Miquel
In recent years, historians and sociologists of science have shown how turn of the century natural history research and its public communication in Barcelona was intrinsically attached to certain political orientations and the historical context. Likewise, the way society perceived bats and promoted their ecological services has been increasingly researched by the community of bat researchers. In this article, I describe attitudes towards and perceptions of bats in the 'public sphere' of Barcelona in that period and examine them using public communication of science and history of science analytical tools. I performed an exhaustive search of the available newspaper and magazine articles using the Catalan and Spanish words for 'bat' in the online search engines of the national Catalan and Spanish libraries from 1888 to 1929. I compiled and reviewed a wide range of periodicals, covering different political orientations and representing several different types of publication. The articles were classified into four different categories. First, bats were commonly used as a symbol to represent the city and right-wing, conservative politics. Second, bats were often linked to negative adjectives that portrayed them as ugly, disgusting or diabolic. Third, many articles made an active effort to stop children chasing and killing bats. And fourth, I also identified a non-organised group of popularisers across the whole media spectrum who promoted what we call today the ecological services provided by bats, and especially their role as agricultural pest controllers. This study provides a better understanding of science popularisation, and specifically, perceptions of and attitudes towards bats during the studied period. This approach illustrates how historical accounts can be used today to improve perceptions of bats and suggest a more complex context of science popularisation.